2013
DOI: 10.1103/physrevlett.111.185301
|View full text |Cite
|
Sign up to set email alerts
|

Realization of the Hofstadter Hamiltonian with Ultracold Atoms in Optical Lattices

Abstract: We demonstrate the experimental implementation of an optical lattice that allows for the generation of large homogeneous and tunable artificial magnetic fields with ultracold atoms. Using laser-assisted tunneling in a tilted optical potential, we engineer spatially dependent complex tunneling amplitudes. Thereby, atoms hopping in the lattice accumulate a phase shift equivalent to the Aharonov-Bohm phase of charged particles in a magnetic field. We determine the local distribution of fluxes through the observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
1,777
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,365 publications
(1,810 citation statements)
references
References 51 publications
13
1,777
0
2
Order By: Relevance
“…Such artificial magnetic fields have been used in quantum gases confined to optical lattices to realize two showcase models of topologically insulating phases, the Hofstadter model in two-dimensions [4][5][6][7] or on a ladder geometry [8] and the Haldane model [9].…”
mentioning
confidence: 99%
“…Such artificial magnetic fields have been used in quantum gases confined to optical lattices to realize two showcase models of topologically insulating phases, the Hofstadter model in two-dimensions [4][5][6][7] or on a ladder geometry [8] and the Haldane model [9].…”
mentioning
confidence: 99%
“…Treating interactions in such a non-perturbative way is difficult in periodically-driven systems [5][6][7][8][9][10], which have received unprecedented attention following the realisation of dynamical localisation [11][12][13][14][15], artificial gauge fields [16][17][18][19][20][21][22], models with topological [23][24][25][26][27][28] and statedependent [29] bands, and spin-orbit coupling [30,31]. In this paper, we consider strongly-interacting periodicallydriven systems and show how the SWT can be extended to derive effective static Hamiltonians of non-equilibrium setups.…”
mentioning
confidence: 99%
“…2, inset), where φ j = φ mn = Φ (m + n), σ ∈ {↑, ↓} ≡ {1, −1}, and we denote the square-lattice position by r j = (m, n). Such spin-sensitive drives are realised in experiments via the Zeeman effect using a periodically-modulated [29] and static [19,20] magnetic-field gradients which couple to atomic hyperfine states. For this protocol,…”
mentioning
confidence: 99%
“…Some aspects of the current work have been explored in previous experiments, including the first atomic-gas simulations of the HarperHofstadter model 6,7 and observations of the chiral motion of particles in effective magnetic fields using synthetic dimensions [8][9][10][11] . But Tai and colleagues' study deepens our understanding of the interplay between interaction effects and the effective magnetic fields.…”
Section: I N D S Ay J L E B L a N Cmentioning
confidence: 99%
“…Bialas and colleagues investigated previously established mouse models of lupus in which there is activation of the type I interferon response 6 . The authors observed that such mice show significant neurological deficits, including poor performance on cognitive and behavioural tasks compared with wildtype animals.…”
Section: S a R A H M C G L A S S O N And Dav I D H U N Tmentioning
confidence: 99%